Psychopathological consequences of maltreatment among children and adolescents: A systematic review of the GxE literature. (November 2018) - Maglione, Dario; Caputi, Marcella; Moretti, Benedetta; Scaini, Simona
Highlights: Child maltreatment is a significant risk factor for developmental psychopathology. Various genes interact with maltreatment in determining dysfunctional outcomes. Multiple genotypes interact with environment in case of maltreatment (GxGxE). A multi-genic approach and a better specification of maltreatment are warranted. Abstract: Background: In the last years, several studies focused on the role of Gene-Environment interactions (GxE) in influencing psychopathological outcomes among maltreated children and adolescents. These studies analysed the effect of different genetic variations. Aims: The aim of the present review is to provide an overview of studies investigating GxE effects among maltreated children and adolescents. Methods and Procedures: A systematic literature review was performed by using the following keywords: "Child maltreatment" and "GxE", "Child maltreatment" and "Psychopathology", "Gene-Environment interaction", "Gene-environment correlation", "GxE and psychopathology", "Childhood trauma" and "Psychiatric symptoms", "Early adverse life events", "Early life stress", "Antisocial behaviour", "Depression", "Internalizing symptoms", through the following electronic databases: PubMed, Scopus and PsycINFO, from 2006 to 2017, finding a total of 31 papers. Outcomes and Results: The present review confirm that maltreatment produces worse psychopathological outcomes (antisocial behaviour, depression, and other psychiatric traits) in subjects with a specific genetic vulnerability. Conclusions and Implications: Comprehending the pathways from child maltreatment to psychopathology in their full complexity will be essential to build efficacious preventive and therapeutic protocols.